The case for the abolition of stamp duty - Sara Luder (Institute for Fiscal Studies (IFS), 2016)
This paper describes how the economic reach of stamp duty is in practice very limited; explains why it nevertheless causes a range of problems; shows how the scope of SDRT could be expanded to cover the transactions in relation to which stamp duty currently raises revenue for the Exchequer; argues that stamp duty can and should on that basis be abolished; and identifies the key benefits that this would have for practitioners, taxpayers and the Exchequer. This paper does not suggest that the existing tax yield from UK stamp taxes on transfers of securities be in any way reduced. It merely proposes a means of streamlining the way in which that tax is collected.
Keywords: 330